ABI End of Initiative - 2024 Progress Deep Dive of the soybean breeding team from IITA - Chigeza, Godfree (International Institute of Tropical Agriculture, 2024)
The presentation summarizes the soybean breeding team's efforts and progress from 2022 to 2024 through a series of questions that highlight the team's breeding achievements. It also discusses the team's successes and challenges during this period.